IMPLEMENTASI MANAJEMEN KURIKULUM DALAM MENINGKATKAN KUALITAS PEMBELAJARANDI MTS NEGERI 1 JAKARTA - Annisa Zakiyyaa; Amaliyah Amaliyah; Diaz Adriansyah; Muhammad Indra Pratama; Nanda Ega Ramdhini (STKIP Pesisir Selatan, 2026)
This study aims to analyze in depth the implementation of curriculum management in improving the quality of learning at MTs Negeri 1 Jakarta, with a focus on the aspects of curriculum planning, organization, implementation, and supervision and their implications for educational quality. This study uses a qualitative approach with a case study type. Primary data were obtained through in-depth interviews with the Madrasah Principal, Deputy Head of Curriculum, and teachers, while secondary data were collected through passive participatory observation and documentation studies of learning tools and official madrasah archives. The results of the study indicate that improving the quality of learning at MTs Negeri 1 Jakarta was successfully achieved through a robust and integrated curriculum management cycle. The planning stage was carried out in a participatory manner through the Curriculum Development Team, followed by structured organization through the madrasah's internal Subject Teacher Meeting (MGMP) to align innovative teaching modules. During the implementation phase, learning is transformed into a student-centered learning model based on higher-order thinking skills and the use of information technology, which aligns with the development of religious character.